Analysis of Menteng City Park as a city identity in DKI Jakarta - Hinijati Widjaja (Budapest International Research and Critics University, 2023)
Every element of a city park will give meaning and function to a place, so that in turn it will form the identity of a city. As a city's identity, its original identity will be polished and eroded due to the proliferation of instant designs, so that there are similarities between one city and another, as a result it is often difficult to recognize its surroundings. The absence of laws or legal provisions protecting urban parks, which should be city assets, makes it difficult to identify the values of urban parks that are related to the history of urban development, so that their role as a city identity is increasingly lost. This study aims to explore the opportunities and challenges in providing legal protection for the Menteng city park, as befits a building that has historical value or as a city identity, already has provisions to be legally protected. The benefit of this research is to produce a profile of the Menteng city park, which has the potential to become a city identity. The research was conducted in the Menteng Park area of DKI Jakarta as a general overview and specifically in the Central Jakarta area. The methods used in data collection are survey methods (interviews, questionnaires and mapping) and archival methods. Data analysis used the assessment method by carrying out several stages, namely compiling a normative framework, compiling weights and scores to determine the level of significance between the variables. The research was conducted in the Menteng Park area of DKI Jakarta as a general overview and specifically in the Central Jakarta area. The methods used in data collection are survey methods (interviews, questionnaires and mapping) and archival methods. Data analysis used the assessment method by carrying out several stages, namely compiling a normative framework, compiling weights and scores to determine the level of significance between the variables. The research was conducted in the Menteng Park area of DKI Jakarta as a general overview and specifically in the Central Jakarta area. The methods used in data collection are survey methods (interviews, questionnaires and mapping) and archival methods. Data analysis used the assessment method by carrying out several stages, namely compiling a normative framework, compiling weights and scores to determine the level of significance between the variables.